Biogas potential of cup plant and willow-leaf sunflower biomass. (15th September 2022) - Stolarski, Mariusz J.; Peni, Dumitru; Dębowski, Marcin
Abstract: Perennial herbaceous crops (PHC) are increasingly often perceived as a competitive biomass source or as a co-substrate for biogas plants. The aim of the study was to determine the dry biomass yield, the biogas and methane production efficiency, potential energy yield and economic analysis for two PHC species, depending on the fertilisation type and nitrogen level in three successive cultivation years. The mean dry matter yield of Silphium perfoliatum was significantly higher (by 19.4%) compared to the mean yield of Helianthus salicifolius . The application of organic (digestate) and mineral fertilisers and a higher nitrogen level have significantly contributed to increasing dry matter yield compared to the plots without fertilisation. However, fertilisation have no significant impact on the biogas or methane efficiency. The highest biogas efficiency for S. perfoliatum and H. salicifolius biomass was 372.8 m 3 Mg −1 DM and 280.9 m 3 Mg −1 DM, respectively. The biogas, methane and energy potential yield of S. perfoliatum was significantly higher (over 50%) compared to the values of H. salicifolius . Meanwhile, the potential income from energy generation from S. perfoliatum was higher by 482%. Therefore, S. perfoliatum proved to be a more prospective PHC species as a biomass source for biogas plants. Highlights: The Silphium perfoliatum yield was higher by 19.4% compared to Helianthus salicifolius The organic and mineral fertilisation increased the biomass yield by 62 and 129% Methane production efficiency from S. perfoliatum was higher by 28.9% Methane yield for S. perfoliatum was higher by 52% compared to H. salicifolius Total energy yield for S. perfoliatum was higher in each fertilisation option